Topical Atropine Induced Acute Psychosis - A case report - Thakuri, Rabindra Singh; Dhakal, Deepak; Tiwari, Sagar; Dahal, Polina; Pokhrel, Kaushal; Bhandari, Sanjeeb (Nepalese Journal of Ophthalmology, 2024)
Introduction: Atropine, an anticholinergic agent is widely used topical agent in ophthalmology practice. We present a case report on central anticholinergic syndrome in a patient receiving topical atropine. Case and observation: An eighty-two years old female who had received a penetrating keratoplasty five years ago in the left eye for non-healing corneal ulcer which had failed within 6 months presented with long standing pain in the eye. She was on topical carboxymethylcellulose 1% and moxifloxacin since the last two weeks and was against the advice for evisceration. We used 1% atropine sulphate eyedrops thrice daily for persistent pain of the left eye. Three days after using topical atropine, she developed acute psychomotor agitation, disorientation, confusion and lack of insight with visual hallucination and lowered level of consciousness. These symptoms resolved after cessation of topical atropine and reappeared on its use. A single dose rechallenge under the supervision of a psychiatrist confirmed that the acute psychosis was induced by topical atropine. The reaction was definite according to Naranjo’s algorithm. Conclusion: The present case shows that a patient on topical atropine can experience central nervous system side effects seen with systemic absorption. The possibilities of such side effects warrants discussion in patients receiving the medication in routine ophthalmology practice.